Molecular phylogenetics and diversification of trap-jaw ants in the genera Anochetus and Odontomachus (Hymenoptera: Formicidae) - Larabee, Fredrick J; Fisher, Brian L; Schmidt, Chris A; Matos-Maraví, Pável; Janda, Milan; Suarez, Andrew V (Molecular phylogenetics and evolution, 2016)
Ants in the genera Anochetus and Odontomachus belong to one of the largest clades in the subfamily Ponerinae, and are one of four lineages of ants possessing spring-loaded "trap-jaws." Here we present results from the first global species-level molecular phylogenetic analysis of these trap-jaw ants, reconstructed from one mitochondrial, one ribosomal RNA, and three nuclear protein-coding genes. Bayesian and likelihood analyses strongly support reciprocal monophyly for the genera Anochetus and Odontomachus. Additionally, we found strong support for seven trap-jaw ant clades (four in Anochetus and three in Odontomachus) mostly concordant with geographic distribution. Ambiguity remains concerning the closest living non-trap-jaw ant relative of the Anochetus+Odontomachus clade, but Bayes factor hypothesis testing strongly suggests that trap-jaw ants evolved from a short mandible ancestor. Ponerine trap-jaw ants originated in the early Eocene (52.5Mya) in either South America or Southeast Asia, where they have radiated rapidly in the last 30million years, and subsequently dispersed multiple times to Africa and Australia. These results will guide future taxonomic work on the group and act as a phylogenetic framework to study the macroevolution of extreme ant mouthpart specialization.
Keywords: Animals; RNA ribozomální 28S; cytochromy b; Phylogeography; South America; RNA, Ribosomal, 28S; Ants; Afrika; Australia; Bayesova věta; Formicidae; Bayes Theorem; Cytochromes b; jihovýchodní Asie; Austrálie; Genetic Variation; Phylogeny; Africa; fylogeografie; Jižní Amerika; zvířata; fylogeneze; genetická variace; Asia, Southeastern